2021
DOI: 10.3390/cancers13040740
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 7 Mediates Inflammation Resolution and Inhibition of Angiogenesis in Non-Small Cell Lung Cancer

Abstract: Pattern recognition receptors (PRR) promote inflammation but also its resolution. We demonstrated that a specific PRR—formyl peptide receptor 1 (FPR1)—sustains an inflammation resolution response with anti-angiogenic and antitumor potential in gastric cancer. Since toll-like receptor 7 (TLR7) is crucial in the physiologic resolution of airway inflammation, we asked whether it could be responsible for pro-resolving and anti-angiogenic responses in non-small cell lung cancer (NSCLC). TLR7 correlated directly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 68 publications
(100 reference statements)
0
13
0
Order By: Relevance
“…Transfectants were selected in medium with 500 ng·mL −1 puromycin [ 10 ]. Human umbilical vein endothelial cells (HUVECs) from Cell Biologics (Chicago, IL, USA) were grown in human endothelial cell medium with the addition of VEGF, heparin, EGF, FGF, hydrocortisone, L‐glutamine, antibiotic/antimycotic solution and FBS according to the manufacturer's instructions (Cell Biologics) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfectants were selected in medium with 500 ng·mL −1 puromycin [ 10 ]. Human umbilical vein endothelial cells (HUVECs) from Cell Biologics (Chicago, IL, USA) were grown in human endothelial cell medium with the addition of VEGF, heparin, EGF, FGF, hydrocortisone, L‐glutamine, antibiotic/antimycotic solution and FBS according to the manufacturer's instructions (Cell Biologics) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…VEGF‐A contents in culture supernatants were measured in duplicate determinations with a commercially available ELISA (R&D Systems). RvD1, LTB 4 , PGE 2 and LXB 4 contents in culture supernatants were measured in triplicate determinations with a commercially available EIA (Cayman Chemical, Ann Arbor, MI, USA) [ 39 ]. Cell culture supernatants were assayed, undiluted for autacoid evaluations and diluted 1 : 5 for VEGF‐A release.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By asking whether similar mechanisms could also intervene in cancers derived from other epithelia, we demonstrated that pro-resolving pathways could also exert anti-angiogenic activity in a lung cancer model; however, in this context, the innate immune receptor that controls SPM production is the Toll-like receptor 7 (TLR7) [ 52 ]. In this model system, TLR7 activation, similarly to FPR1 in the GI tract, sustains the increased expression of the enzymes responsible for SPMs biosynthesis, the increased secretion of SPMs from cancer cells, the augmented expression of SPM receptors, and finally the reduction of the angiogenic potential of lung cancer cells [ 52 ].…”
Section: Effects Of Spms On the Tumor Vascular Bedmentioning
confidence: 99%
“…A key function in modulating the inflammatory response has been defined for FPRs: they are classically able to sustain the inflammatory response, but, as a function of the context and/or the agonist, they can intervene in the resolution of the inflammatory response (17)(18)(19). This activity seems to be common to other PRRs (20,21). This key role of FPRs in modulating the induction, the amplification, and the following physiologic resolution phase of the inflammatory responses prompted some research groups to study FPRs role in diseases whose pathogenesis is strictly linked to a strong imbalance between the inflammation and its resolution.…”
Section: Introductionmentioning
confidence: 99%